Alocação negociada da água no Ceará: proposta metodológica para a tomada de decisão em cenário de escassez - Abreu, Inah Maria de (2015)
The water, especially for being a common use, with reduced current availability in the world, makes your allocation a social dilemma that requires decisions and make your rational management essential. This thesis arises from the interest in developing the proposition, with involvement of social agents of the participatory management of water resources of the State of Ceará-Brazil. The methodology is compartmentalized into three steps: secondary data collection; the primary indicators, which it intends to obtain empirical data, on the basis of: participation in meetings of negotiated allocation of water, in the application of questionnaires, interviews and cooperative games with members of social arena and conducting social experiment; Finally, the treatment of information and indications that integrates, correlates, and analyzes the information and guides collected in Office and field. The consultation, through application of the questionnaires, together with members of the 12 (twelve) committees of the catchment area of the State of Ceará pointed as a result to guarantee future of use of water stored in a reservoir, in times of scarcity, as the primary motivation that encourages taking rational attitudes on water use. The results of the application of cooperative games bring out the existence of factors that interfere in the decision-making of the members of the watershed committees. Based on the data collected and interviews conducted, devised the "cognitive Map added" where were identified the strategies that make up the path to the meeting of attributes that can be negotiated for the allocation of water. Also indicated result of social experiment conducted in river basin Committee, where he obtained the members that sustainable exploitation of water resources by the water users sectors, is essential criterion for establishing order of preference in the use of water in situations of scarcity. The criterion inventoried, so associated with the results of the consultation and of the cognitive mapping of the river basin committees, is in line with the proposal for allocation of water, composed essentially of two strategies: first, social participation based on the planning steps for the preparation of the scenarios of reservoir systems operation, therefore, with emphasis on dialogue and involvement of society , and the other, directed to the application between users of the irrigation sector. Finally, one of the suggestions gathered was suggested the insertion of cooperative games tied to the process of formation and training in water resources management for members of the CBHs, as required and improved their dialogue, respect and trust among the social sectors involved.